An ordered set of Nörlund means - J. Defranza (International Journal of Mathematics and Mathematical Sciences)
Nörlund methods of summability are studied as mappings from ℓ1 into ℓ1. Those Nörlund methods that map ℓ1 into ℓ1 are characterized. Inclusion results are given and a class of Nörlund methods is shown to form an ordered abelian semigroup.